Presença de alcalóides β-carbolínicos no Rami ou Hami (Bebida de índio) - Wolter Filho, Wilson; Cabral, José Augusto da Silva; Rocha, Arnaldo Imbiriba da (Acta Amazonica, 1982)
From a drink widely utilized by the Indian nations of western Amazonia, hallucinogenic, two β-carbolinic alkaloids have been isolated.